Flik: design tool on adaptation process for non-designers in a rehabilitation setting - Mat Yusof, Nurhikma; Raja Ahmad Effendi, Raja Ahmad Azmeer; Dolah, Mohd Shahrizal; Yahaya, Mohd Faiz; Bolong, Jusang; Haron, Nuzul Azam; Harun, Azahar (Universiti Putra Malaysia Press, 2020)
Adaptation is a key practice in rehabilitation that assists the client’s recovery following a disease or injury. Lack of design skills and problem solutions has turned the process into a fuzzy front, especially for entry level therapists. Furthermore, the low adaptation tool rate usage has listed several contributing factors, which includes non-compliance, uncomfortable designs, low aesthetic values, scant personal acceptance, inadequate instructions, and training. However, the design thinking concept has seen an increase with the adoption of interdisciplinary studies in recent years. From the aspect of innovation, the concept seems difficult to implement without close supervision from design experts. That said, a proper design process shall be introduced to therapists for better adaptive tools in the future. The purpose of this study is to assist in the adaptation process for occupational therapy as a self-assisting tool through the design process. This method is a convergence of OT and design practice into a design-health system, which resulted in the development of FLIK (Functionled Innovation Kit), that supports non-designers (therapists) while performing adaptation activities, albeit not possessing formal design knowledge. Overall, this study investigates the opportunity of an interdisciplinary collaboration between design and health sectors; as well as to enhance work practices which is imperative for more effective services and recoveries in future.